2023
DOI: 10.21203/rs.3.rs-2470790/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pattern of CD4 + T cell recovery and determinants of HIV infected individuals receiving highly active antiretroviral treatment in Mekelle Hospital, Tigray Northern Ethiopia; Retrospective study

Abstract: Background: With the advent of antiretroviral treatment, HIV related morbidity and mortality have tremendously decreased. However, some HIV patients on ART don’t optimally respond to the ART regimen to restore the immunity. This study was aimed to determine the pattern of CD4+ T cell recovery and determinants of HIV infected individuals receiving the ART in Mekelle Hospital, Tigray northern Ethiopia. Methods: A hospital based retrospective cross-sectional study was conducted from January, 2010 to August, July … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 39 publications
0
1
0
Order By: Relevance
“…This finding was supported by studies conducted in Asia, China and Ethiopia. 18 , 24 , 30 , 31 Nevertheless, a study conducted in southern Ethiopia reported a higher baseline CD4 cell count as a risk factor for immunological failure. 32 This inconsistency might be due to the difference in CD4 cut-off points used to define immunological failure (WHO 2016 vs WHO 2010, which defines immunological failure when CD4 levels remain below 100 cells/mm3 and/or 50% fall from the on-treatment peak value).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding was supported by studies conducted in Asia, China and Ethiopia. 18 , 24 , 30 , 31 Nevertheless, a study conducted in southern Ethiopia reported a higher baseline CD4 cell count as a risk factor for immunological failure. 32 This inconsistency might be due to the difference in CD4 cut-off points used to define immunological failure (WHO 2016 vs WHO 2010, which defines immunological failure when CD4 levels remain below 100 cells/mm3 and/or 50% fall from the on-treatment peak value).…”
Section: Discussionmentioning
confidence: 99%
“…This finding is supported by previous studies conducted in Asia and Ethiopia. 18,24 Similarly, patients aged ≥50 years were nearly three times more likely to develop immunological failure than those aged <50 years were. This was in line with studies conducted in Asia, Israel, and the USA 18,25,26 which showed a slower increase in CD4 + cell counts in patients aged ≥50 years than in their younger counterparts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation